Process Optimization of Experimental Variables Using Plackett-Burman Design for Decolourisation of Reactive Blue 222 by a Novel Bacterial Consortium Isolated from the Gut of Termites: Dye Decolourisation by Bacterial Consortium from Termite Gut (Biological Sciences - PJSIR, 2009)
Bacterial consortium derived from termite was tested for its efficiency to decolourise Reactive Blue 222 aerobically. The central composite design matrix and response surface methodology (RSM) were applied to design experiments for the assessment of interactive effects of four most important operating variables viz., pH (3.0-11.0), agitation (300 rpm), temperature (20-60 °C) and glucose (0.1-0.5 g/litre) on the biodegradation of Reactive Blue 222 out of eleven different variables. Optimisation was achieved using the Plackett-Burman statistical design. A regression coefficient between variables and the response indicated excellent evaluation of experimental data by the Stat-Ease package. The experimental values were in good agreement with the predicted ones and the model was highly significant, correlation coefficient being 0.89. RSM indicated that pH 7.0 at static condition; temperature at 20 °C and a glucose concentration of 0.50 g/litre resulted in 99.21% decolourisation.